2009
DOI: 10.2169/internalmedicine.48.2490
|View full text |Cite
|
Sign up to set email alerts
|

Gradual Progression of Interstitial Pneumonia Induced by Bepridil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
1
5
1
Order By: Relevance
“…The fact that interstitial pneumonia was induced at a low dose of bepridil (100 mg/day) supports an immunoallergic mechanism rather than a pulmonary toxicity mechanism. In the present case, the dose of bepridil was lower than those in previously reported cases (150-400 mg/day) [3] and it was given for a shorter period. An immunoallergic mechanism would cause a small dose of bepridil to induce interstitial pneumonia.…”
Section: Discussioncontrasting
confidence: 77%
See 2 more Smart Citations
“…The fact that interstitial pneumonia was induced at a low dose of bepridil (100 mg/day) supports an immunoallergic mechanism rather than a pulmonary toxicity mechanism. In the present case, the dose of bepridil was lower than those in previously reported cases (150-400 mg/day) [3] and it was given for a shorter period. An immunoallergic mechanism would cause a small dose of bepridil to induce interstitial pneumonia.…”
Section: Discussioncontrasting
confidence: 77%
“…Our patient experienced respiratory symptoms and fever on the fourth day when bepridil was administered for the third time. The onset of bepridil‐induced interstitial pneumonia was earlier in our case than in previously reported cases, in which patients developed bepridil‐induced interstitial pneumonia at any time from 14 days to >200 days after administration of bepridil [3]. In the present case, we noted that the underlying mechanism of bepridil‐induced interstitial pneumonia may have involved an immunoallergic reaction rather than pulmonary toxicity resulting from drug accumulation, as is sometimes the case with amiodarone.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…This is the first study reporting the incidence of bepridilinduced pulmonary toxicity, and the incidence was 3.60% (eight out of 222 cases) in our patient population. Six prior cases of bepridil-induced pulmonary toxicity had been reported in the English literature [2], and one case of acute interstitial pneumonia had also been reported as a side effect in a randomized study of amiodarone and bepridil out of the 20 patients in the bepridil-arm [5]. The diagnosis of drug-induced pulmonary toxicities, including those due to bepridil, is associated with uncertainties, largely because of the restrictions regarding the re-challenge of patients, and the diagnostic criteria we use are generally non-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Bepridil is a Na + , K + , and Ca 2+ channel blocker that is effective for atrial fibrillation (AF), and is currently used as a second‐line therapeutic agent for AF in Japan. Interstitial pneumonia (IP) is a well‐known adverse effect associated with amiodarone, and sporadic cases of bepridil‐induced IP (BIP) have been reported [1–6]. Previous studies have reported that the interval from bepridil administration to the onset of dyspnea due to IP was 4–60 days, except for the patient described by Suzuki et al [5], who developed dyspnea 226 days after starting treatment.…”
Section: Introductionmentioning
confidence: 99%